2018
DOI: 10.3389/fphar.2018.00734
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of L-3-n-Butylphthalide in Cognitive Function and Dysthymic Disorders in Mouse With Chronic Epilepsy

Abstract: Epilepsy is a common neurological disease with recurrent seizures and neurobehavioral comorbidities, including cognitive impairment and psychiatric disorders. Recent studies suggest that L-3-n-butylphthalide (NBP), an extract from the seeds of Apium graveolens Linn. (Chinese celery), ameliorates cognitive dysfunction in ischemia and/or Alzheimer’s disease animal models. However, little is known about the role of NBP in epilepsy and the associated comorbidities. Here, using a pilocarpine-induced chronic epilept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 64 publications
1
20
0
Order By: Relevance
“…Mice used for the PPI study were part of a longer study and got injected intraperitoneal with a solution of 5% Tween80 in 0,9% sodium chloride daily for 6 weeks, starting at 3 months. Tween-80 is commonly used as a vehicle to evaluate the behavioral effects of experimental drugs without apparent adverse side effects [30][31][32][33][34][35][36][37][38]. All animals were handled according to the guidelines of the 'Society for Laboratory Animals Science' (GV-SOLAS) and the guidelines of the 'Federation of European Laboratory Animal Science Association' (FELASA).…”
Section: Tg4-42 Transgenic Micementioning
confidence: 99%
“…Mice used for the PPI study were part of a longer study and got injected intraperitoneal with a solution of 5% Tween80 in 0,9% sodium chloride daily for 6 weeks, starting at 3 months. Tween-80 is commonly used as a vehicle to evaluate the behavioral effects of experimental drugs without apparent adverse side effects [30][31][32][33][34][35][36][37][38]. All animals were handled according to the guidelines of the 'Society for Laboratory Animals Science' (GV-SOLAS) and the guidelines of the 'Federation of European Laboratory Animal Science Association' (FELASA).…”
Section: Tg4-42 Transgenic Micementioning
confidence: 99%
“…In animal models of cerebral apoplexy, NBP was mainly used for inhibiting platelet aggregation, reducing thrombosis, improving microcirculation, reducing the volume of cerebral infarction, resisting oxidative stress, protecting mitochondrial function, reducing neuronal apoptosis, alleviating inflammatory reaction, mediating autophagy of nerve cells, promoting neurogenesis and targeting in several pathophysiological mechanisms, which are mainly reflected in its obvious neuroprotective effect. [16][17][18][19][20][21][22][23][24][25][26] After further studies on its application, it was found that the beneficial effects of NBP are beyond those of apoplexy. Especially in neurodegenerative disease fields, it was found that NBP and its ramifications have unique function and effects in AD, vascular dementia (VaD), PD, ALS and DEACMP treatment.…”
Section: Introductionmentioning
confidence: 99%
“…NBP,as an emerging anti-ischemic drug,inhibits platelet aggregation,reduces thrombosis,improves microcirculation,reduces cerebral infarction volume,resists oxidative stress,protects mitochondrial function,reduces neuronal apoptosis,and reduces in ammation,response and mediate autophagy of neurons,promote neurogenesis,etc in stroke animal models.It exerts multitargeting effects on a variety of pathophysiological mechanisms and shows obvious neuroprotective effects [7][8][9][10][11][12][13][14][15][16][17][18][19][20] .It has been found that its bene cial effect is far beyond the therapeutic scope of stroke [21,22] after further research and application of its application.Especially in the eld of neurodegenerative diseases,people have found that NBP and its derivatives are used in AD,VD,Parkinson's disease (PD) and Amyotrophic Lateral Sclerosis (ALS) all have unique effects and e cacy [7,[23][24][25] .…”
Section: Introductionmentioning
confidence: 99%